Rosses Point revisited - Woodman, Peter C.
The re-evaluation of artefacts sometimes reveals a long history of misinterpretation. Here Peter Woodman re-assesses stone tools from western Ireland which have important lessons for how our personal biases influence our interpretation of lithic assemblages.